Allele Percentage of the BRAF V600E Mutation in Papillary Thyroid Carcinomas and Corresponding Lymph Node Metastases: No Evidence for a Role in Tumor Progression - Gandolfi, Greta; Sancisi, Valentina; Torricelli, Federica; Ragazzi, Moira; Frasoldati, Andrea; Piana, Simonetta; Ciarrocchi, Alessia (The journal of clinical endocrinology and metabolism, 2013)
Context:The relevance of the BRAF V600E mutation in papillary thyroid carcinoma (PTC) as a negative prognostic factor is a subject of intense debate. This mutation has been associated with several clinicopathological features, but the lack of consistency among data does not support its usefulness as marker of tumor aggressiveness and poorer outcome. Due to the genetic heterogeneity of the tumor, both the occurrence and the allele percentage of the BRAF mutation should be considered to unravel this controversy.Objective:We aimed to evaluate the impact of the BRAF V600E mutation occurrence and the allele percentage on the metastatic process in PTCs.Study Design:The presence and allele percentage of the BRAF mutation were determined by pyrosequencing in 132 cases of well-differentiated PTCs with (n = 37) or without lymph node metastases (LNMs) (n = 95) and in 40 LNMs matched with 35 PTCs.Results:No significant differences were observed in either the occurrence or the allele percentage of V600E mutation between the 2 groups of PTCs with or without LNMs. The LNMs were heterogeneous for the V600E mutation as the primary lesions.Conclusions:In this study, the occurrence and percentage of the BRAF V600E mutated allele was not preferentially associated with the development of metastases and the average mutated allele percentage decreased as the tumor progresses from the primary site to the lymph node metastatic sites. These observations support the need to reevaluate the role of the BRAF V600E mutation as a negative prognostic marker in PTCs.